2021
DOI: 10.3390/sym13101861
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning Based Prognosis Approach for Remaining Useful Life Prediction of Turbofan Engine

Abstract: The entire life cycle of a turbofan engine is a type of asymmetrical process in which each engine part has different characteristics. Extracting and modeling the engine symmetry characteristics is significant in improving remaining useful life (RUL) predictions for aircraft components, and it is critical for an effective and reliable maintenance strategy. Such predictions can improve the maximum operating availability and reduce maintenance costs. Due to the high nonlinearity and complexity of mechanical syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…They performed a case study by estimating the RUL of turbofan engine on four subsets of C-MAPPS benchmark dataset. The main limitation of this work [40], the uncertainty inherent in their DL model was not quantified. Khawaja, Vachtsevanos, and Wu [41] developed a confidence prediction NN method with a confidence distribution node to solve the downside that the confidence limits of RUL prediction cannot generally be explicitly acquired with NN techniques.…”
Section: Background and Related Workmentioning
confidence: 95%
See 1 more Smart Citation
“…They performed a case study by estimating the RUL of turbofan engine on four subsets of C-MAPPS benchmark dataset. The main limitation of this work [40], the uncertainty inherent in their DL model was not quantified. Khawaja, Vachtsevanos, and Wu [41] developed a confidence prediction NN method with a confidence distribution node to solve the downside that the confidence limits of RUL prediction cannot generally be explicitly acquired with NN techniques.…”
Section: Background and Related Workmentioning
confidence: 95%
“…Huang et al [39] used the classic multi-layer perceptron (MLP) approach to predict the RUL of bearings in laboratory testing and found that the prediction results outperformed reliability-based alternatives. Muneer et al [40] suggested an attention based DCNN model with time window approach to cope with the degradation and reliability of time-series forecasting problem. They performed a case study by estimating the RUL of turbofan engine on four subsets of C-MAPPS benchmark dataset.…”
Section: Background and Related Workmentioning
confidence: 99%
“…It is a nonlinear model where any prior knowledge of the relationship between input and output is needed [29]. Therefore, DLNN gives good results for pattern recognition [30], [31], sequence prediction [32],  ISSN: 2088-8708 Int J Elec & Comp Eng, Vol. 12, No.…”
Section: Deep Learning Neural Network (Dlnn)mentioning
confidence: 99%
“…A deep CNN approach with a time window [9] was applied to normalized raw C-MAPSS data. Muneer et al [24] combined deep CNN with an attention mechanism to extract highly abstract degradation and trend features. Temporal convolution expanded the receptive field for long sequences to improve the prediction performance [25].…”
Section: Introductionmentioning
confidence: 99%